Temperature-dependent variations in under-canopy herbaceous foliar diseases following shrub encroachment in grasslands - Yilin Dang; Peng Zhang; Peixi Jiang; Junsheng Ke; Yao Xiao; Yingying Zhu; Mu Liu; Minjie Li; Jihua Wu; Jianquan Liu; Bin Tian; Xiang Liu (Nature Communications)
Abstract Shrub encroachment into grasslands poses a global concern, impacting species biodiversity and ecosystem functioning. Yet, the effect of shrub encroachment on herbaceous diseases and the dependence of that effect on climatic factors remain ambiguous. This study spans over 4,000 km, examining significant variability in temperature and precipitation. Our findings reveal that herbaceous plant species richness diminishes the pathogen load of foliar fungal diseases of herbaceous plants in both shrub and grassland patches. Temperature emerges as the primary driver of variations in herbaceous biomass and pathogen load within herbaceous plant communities. Disparities in herbaceous biomass between shrub and grassland patches elucidate changes in pathogen load. In colder regions, shrub encroachment diminishes herbaceous biomass and pathogen load. Conversely, in warmer regions, shrubs either do not reduce or even amplify pathogen load. These discoveries underscore the necessity for adaptive management strategies tailored to specific shrub encroachment scenarios.